How to Become a Million Dollar Real Estate Agent in Your First Year : What Smart Agents Need to Know Explained Simply. - Alvis, Susan (Atlantic Publishing Group, 2016)
Packed with new material and updated for the 2016 (and beyond) market, this guide will show you how to find properties, how to list them, how to sell them, and how to get your commission.